(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Economic growth is one of the ultimate goals of any economic system. The relationship between the development of the regions and economic growth of the state is a subject of long-time debates. The regional development is influenced by many factors that act differently depending on the region. The economic environment is characterized by non-linear turbulent changes and the regions face everyday challenges. Each region has its own competitive advantages that can be used for regional development and thus to reducing regional disparities. Regions must be able to adapt to new challenges and new economic environment through its policies and strategies. Regions can use different types of assistance for their development, e.g. in the form of financial instruments, innovative activities, innovative strategies or new policies geared to promoting regional development. Regional innovation strategies are systematic, goal-oriented exercises carried out by regional partnerships. The goal of research is to analyse actual position of the Slovak republic and its regions in regional innovation performance. A wide range of scientific methods and procedures were used in processing research. The first chapter focuses on the definition of terms such as regional development, regional disparity, cohesion policy and regional innovation strategy. Results part consists of the key findings and is prepared by using a comparative and historical descriptive analysis. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.